Brand authenticity: An integrative framework and measurement scale - Morhart, Felicitas; Malär, Lucia; Guèvremont, Amélie; Girardin, Florent; Grohmann, Bianca (Journal of Consumer Psychology, 2015)
AbstractAlthough brand authenticity is gaining increasing interest in consumer behavior research and managerial practice, literature on its measurement and contribution to branding theory is still limited. This article develops an integrative framework of the concept of brand authenticity and reports the development and validation of a scale measuring consumers' perceived brand authenticity (PBA). A multi‐phase scale development process resulted in a 15‐item PBA scale measuring four dimensions: credibility, integrity, symbolism, and continuity. This scale is reliable across different brands and cultural contexts. We find that brand authenticity perceptions are influenced by indexical, existential, and iconic cues, whereby some of the latters' influence is moderated by consumers' level of marketing skepticism. Results also suggest that PBA increases emotional brand attachment and word‐of‐mouth, and that it drives brand choice likelihood through self‐congruence for consumers high in self‐authenticity.